Advances in the diagnosis, assessment and outcome of Takayasu's arteritis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER LONDON LTD, 2013)
Takayasu's arteritis (TAK) is a rare, chronic large-vessel vasculitis (LVV) that predominantly affects aorta, its major branches, and the pulmonary arteries. Segmental stenosis, occlusion, dilatation, or aneurysm formation may occur in the vessel wall during the course of the disease. The vascular involvement can be shown with different imaging modalities to make the diagnosis of TAK. Conventional angiography, the gold standard method for initial diagnosis, seems to be replaced with the new imaging modalities such as magnetic resonance angiography (MRA) and F-18-fluorodeoxyglucose positron emission tomography (FDG-PET) in recent years. The data coming from the new studies support that MRA and FDG-PET are also promising for the assessment of disease activity. Prognosis is possibly getting better with lower mortality in recent years; however, it is difficult to assess the widely different vascular intervention rates among the clinical series. Leflunomide, TNF-alpha antagonists, and tocilizumab are new options in patients resistant to conventional therapies. There is a clear need to develop a validated set of outcome measures for use in clinical trials of TAK. The OMERACT Vasculitis Working Group has taken on this task and aims to develop a core set of outcomes for LVV.
Keywords: Disease assessment; Outcome; Takayasu's arteritis; POSITRON-EMISSION-TOMOGRAPHY; LARGE-VESSEL VASCULITIS; QUALITY-OF-LIFE; DISEASE-ACTIVITY; F-18-FDG PET; THERAPY; EXTENT; INDEX; INVOLVEMENT; LIMITATIONS